2013
DOI: 10.1002/ejoc.201201580
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of α‐Glycosyl Azides by TMSOTf‐Mediated Ring Opening of 1,6‐Anhydro Sugars

Abstract: Access to α‐glycosyl azides in modest to high diastereoselectivity by way of TMSN3 ring‐opening of 1,6‐anhydro sugars mediated by TMSOTf is reported. The reaction tolerates a wide variety of functional groups including alcohol, alkyne, azide and ester groups. The efficient synthesis of a pseudopentasaccharide in five steps from commercially available levoglucosan by way of a “click‐click” approach is presented to highlight the interest of the TMSN3 ring‐opening reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…1,6-Anhydro-2,3,4-tri-O-(triisopropylsilylpropargyl)-β-D-glucopyranose ( 2 ). To a solution of 1,6-Anhydro-2,3,4-tri- O -propargyl- β -D-glucopyranose [ 3 ] (1 equiv., 675 mg, 2.44 mmol) in THF (60.9 mL) at −70 °C was added LiHMDS (4 equiv., 1 M, 9.77 mL, 9.77 mmol) dropwise. Then after 20 min TIPSCl (4 equiv., 1.94 g, 2.16 mL, 9.77 mmol) was added dropwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6-Anhydro-2,3,4-tri-O-(triisopropylsilylpropargyl)-β-D-glucopyranose ( 2 ). To a solution of 1,6-Anhydro-2,3,4-tri- O -propargyl- β -D-glucopyranose [ 3 ] (1 equiv., 675 mg, 2.44 mmol) in THF (60.9 mL) at −70 °C was added LiHMDS (4 equiv., 1 M, 9.77 mL, 9.77 mmol) dropwise. Then after 20 min TIPSCl (4 equiv., 1.94 g, 2.16 mL, 9.77 mmol) was added dropwise.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we have recently reported a molecular Lego approach for the synthesis of functionalized cyclic and acyclic neo-oligosaccharides [ 2 ]. Our strategy was based on the linkage of bifunctional building blocks by Cu(I)-catalyzed azide−alkyne cycloaddition, the reducing end of the sugars being activated as a glycosyl azide and masked as a 1,6-anhydro sugar [ 2 , 3 ]. To explore the interest of thiol-click chemistry for such modular strategies [ 4 , 5 ], we needed to synthesize thioglycoside 1 ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[9] In 2013, Compain et al reported the stereocontrolled synthesis of α-glycosyl azides by way of TMSOTf-mediated ring-opening of 1,6-anhydro sugars with a large excess of TMSN 3 (Scheme 1a). [10] According to the absolute configuration and substitution at C-2, moderate to high level of diastereoselectivity could be achieved (up to de > 98 % in the D-gluco series). The αselectivity observed may be explained by assuming a preferential nucleophilic attack along axial trajectories on the most reactive/favored half-chair of the glycosyl cation intermediate (Scheme 1b).…”
Section: Ring-opening With N-nucleophilesmentioning
confidence: 98%
“…The αselectivity observed may be explained by assuming a preferential nucleophilic attack along axial trajectories on the most reactive/favored half-chair of the glycosyl cation intermediate (Scheme 1b). [10,11] The α-glycosyl azides were formed with a high level of chemoselectivity and functional group tolerance. Reaction scope studies reported independently by Compain [10] and few years after by Zhu [12] showed that the reaction is compatible with a wide range of functional groups including alcohol, alkyne, and ester groups.…”
Section: Ring-opening With N-nucleophilesmentioning
confidence: 99%
“…Glycosyl azides can be accessed from the corresponding glycosyl halides [ 37 40 ] by nucleophilic displacement with NaN 3 or using trimethylsilyl azide in the presence of a phase transfer catalyst [ 41 45 ]. More commonly, glycosyl azides are synthesized from per- O -acetylated sugars using trimethylsilyl azide in the presence of a variety of Lewis acids such as SnCl 4 [ 46 ], TiCl 4 [ 47 48 ], BF 3 ·OEt 2 [ 49 ] , TMSOTf [ 50 51 ], etc. However, at higher concentration Lewis acids can potentially lead to slow anomerization [ 52 ].…”
Section: Introductionmentioning
confidence: 99%